Acetylshikonin suppressed growth of colorectal tumour tissue and cells by inhibiting the intracellular kinase, T‐lymphokine‐activated killer cell‐originated protein kinase. (10th April 2020) - Zhao, Ran; Choi, Bu Young; Wei, Lixiao; Fredimoses, Mangaladoss; Yin, Fanxiang; Fu, Xiaorong; Chen, Hanyong; Liu, Kangdong; Kundu, Joydeb Kumar; Dong, Zigang; Lee, Mee‐Hyun
Abstract : Background and Purpose: Overexpression or aberrant activation of the T‐lymphokine‐activated killer cell‐originated protein kinase (TOPK) promotes gene expression and growth of solid tumours, implying that TOPK would be a rational target in developing novel anticancer drugs. Acetylshikonin, a diterpenoid compound isolated from Lithospermum erythrorhizon root, exerts a range of biological activities. Here we have investigated whether acetylshikonin, by acting as an inhibitor of TOPK, can attenuate the proliferation of colorectal cancer cells and the growth of patient‐derived tumours, in vitro and in vivo. Experimental Approach: Targets of acetylshikonin, were identified using kinase profiling analysis, kinetic/binding assay, and computational docking analysis and knock‐down techniques. Effects of acetylshikonin on colorectal cancer growth and the underlying mechanisms were evaluated in cell proliferation assays, propidium iodide and annexin‐V staining analyses and western blots. Patient‐derived tumour xenografts in mice (PDX) and immunohistochemistry were used to assess anti‐tumour effects of acetylshikonin. Key Results: Acetylshikonin directly inhibited TOPK activity, interacting with the ATP‐binding pocket of TOPK. Acetylshikonin suppressed cell proliferation by inducing cell cycle arrest at the G1 phase, stimulated apoptosis, and increased the expression of apoptotic biomarkers in colorectal cancer cell lines. Mechanistically, acetylshikonin diminished the phosphorylation and activation of TOPK signalling. Furthermore, acetylshikonin decreased the volume of PDX tumours and reduced the expression of TOPK signalling pathway in xenograft tumours. Conclusion and Implications: Acetylshikonin suppressed growth of colorectal cancer cells by attenuating TOPK signalling. Targeted inhibition of TOPK by acetylshikonin might be a promising new approach to the treatment of colorectal cancer.